Le Kivu dans la guerre : acteurs et enjeux - Roland Pourtier (EchoGéo)
Once again, it’s war time in Kivu. In spite of the United Nation’s mission (MONUC) that tries to put an end to the turmoil in the eastern part of the Democratic Republic of Congo, an other conflict has popped up in the heart of the African continent. In this region thousands of people have been killed and millions of others removed from their birthplace by the permanent troubles that have prevailed since the burst of violence occurred in the Great lakes regions in 1994. In the mean time, the FAR, leaded by Paul Kagame has won the civil war in Rwanda, and the core of the violence vortex has switched to the DRC where a part of the hutu resistant movement has established its bases and from where it keeps assaulting the Rwandan territory. Close to the Rwandan boundary, the Kivu province gives access to the Nile river basin and many strategic mineral resources. Beyond the scandal caused by images of violence, riots and rape are not so new. It has been like this since the early 1980’, from Masisi (east of Goma) to Kivu (around Bukavu). One can’t understand what’s cooking in the eastern part of the RDC unless we consider the deep rooted causes of so many tensions. This article is an attempt to explain why these mountains are a powder magazine in the heart of a highly populated region.